2019
DOI: 10.1186/s40425-019-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyamidotriazole combined with IDO1-Kyn-AhR pathway inhibitors profoundly enhances cancer immunotherapy

Abstract: BackgroundCancer immunotherapy has generated significant excitement, mainly as a result of the development of immune checkpoint inhibitors. The blockade of PD-1 or its ligand with antibodies has resulted in impressive clinical efficacy. However, a subset of patients does not respond to biologic therapeutics, and another subset suffers from severe immune-related adverse events in certain cases. The modulation of the immune system with small molecules might yield surprising benefits.MethodsCD8+ cells were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
2
30
0
4
Order By: Relevance
“…In the early stage of tumorigenesis, CAI exerted a signi cant anti-cancer effect but in the stage of tumor relapse or progression, the role of CAI was relatively weakened, which can be observed in our animal experiments and previous clinical studies [20,21]. Recently we found that longterm CAI treatment produces a suppressive effect on CD8 + T cells through activation of IDO-Kyn-AhR cascade, which contributes to a weakened immune response in tumor initiation, growth and metastasis [22]. Providing evidence that the effects that hamper the in vivo anti-tumor capability of CAI might occur through the IDO-Kyn-AhR cascade.…”
Section: Introductionsupporting
confidence: 77%
“…In the early stage of tumorigenesis, CAI exerted a signi cant anti-cancer effect but in the stage of tumor relapse or progression, the role of CAI was relatively weakened, which can be observed in our animal experiments and previous clinical studies [20,21]. Recently we found that longterm CAI treatment produces a suppressive effect on CD8 + T cells through activation of IDO-Kyn-AhR cascade, which contributes to a weakened immune response in tumor initiation, growth and metastasis [22]. Providing evidence that the effects that hamper the in vivo anti-tumor capability of CAI might occur through the IDO-Kyn-AhR cascade.…”
Section: Introductionsupporting
confidence: 77%
“…This suggests that inhibition of Trp breakdown or KYNs/AhR signaling might be a promising therapeutic target in cancer to modulate the immunosuppressive tumor microenvironment. Jing et al have shown that combining carboxyamidotriazole (anti-cancer molecule) with IDO1-Kyn-AhR pathway inhibitors profoundly enhanced cancer immunotherapy in primary tumor cells isolated from tumor-bearing mice [ 124 ].…”
Section: Tryptophan Metabolism Pathways and Ahr In Diseasementioning
confidence: 99%
“…Chen et al (2017) reported that the combination of sorafenib and carboxyamidotriazole inhibited the proliferation of nonsmall cell lung cancer cells of A549 and NCI-H1975 lines in vitro, and Lewis lung carcinoma bearing mice [4]. The application of carboxyamidotriazole doi: https://doi.org/10.15407/ubj92.05.023 in the combination with 3′,4′-dimethoxyflavone or carboxyamidotriazole with 1-methyl-L-tryptophan resulted in higher anticancer activity than it was found for a single agent treatment [2].…”
mentioning
confidence: 99%
“…1) capable of binding to and inhibiting of the non-voltage-operated Ca 2+ channels and blocking cellular Ca 2+ influx and release, cause a disruption of calcium channel-mediated signal transduction and inhibition of vascular endothelial growth factor signalling, endothelial proliferation, and angiogenesis [1]. This agent is also widely used in cancer therapy [2][3][4]. Carboxyamidotriazole inhibits growth of H345 small cell lung cancer cells via VEGF-dependent pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation